Growth of mixed and intact litters compared - B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1970)
Mixing litters after weaning did not significantly affect rate of gain or efficiency of growing pigs. Weight gains were similar (1.57 or 1.49) for mixed litters and intact litters during a 28-day post-weaning trial.; Swine Day, Manhattan, KS, October 1, 1970
Keywords: Swine day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 163; Swine; Growth; Mixed vs. intact litters